Evaluating The Effectiveness of The 'Guess Who/What' Game in Improving EFL Students' Speaking Skills - Rery, Nurul Masyithah; Putri, Hikmah Zalifah; Agustiani, Aulia (Innovative: Journal Of Social Science Research, 2025)
Speaking is a critical skill in English as a Foreign Language (EFL) learning, yet many learners face challenges in fluency, accuracy, vocabulary, and pronunciation. This study investigates the effectiveness of the "Guess Who/What" game in improving the speaking performance of junior high school EFL students, focusing on descriptive texts. Using a quasi-experimental design, pre-test and post-test scores from 32 students were analyzed quantitatively. Two trained raters assessed performance using a standardized rubric across four criteria. Inter-rater reliability was calculated with Cohen's Kappa (κ = 0.88 for the pre-test and κ = 0.92 for the post-test). Results indicated significant improvements in all criteria, with the greatest gains in vocabulary (+15.6 points). A paired-sample t-test confirmed the statistical significance of the improvement (t = 13.45, p < 0.001). The findings highlight the potential of interactive games to enhance EFL speaking performance and provide practical insights for classroom implementation.